Inflation, Inequality, and Social Conflict - Crowe, Christopher (IMF Working Papers; Working Paper ;, 2006)
This paper presents and then tests a political economy model to analyze the observed positive relationship between income inequality and inflation. The model's key features are unequal access to both inflation-hedging opportunities and the political process. The model predicts that inequality and 'elite bias' in the political system interact to create incentives for inflation. The paper's empirical section focuses on this predicted interaction effect. The identification strategy involves using the end of the Cold War as a source of exogenous variation in the political environment. It finds robust evidence in support of the model.